2003
DOI: 10.1140/epje/i2002-10109-x
|View full text |Cite
|
Sign up to set email alerts
|

Self-organization of N* inclusions in SmC* free-standing films

Abstract: The behaviour of freely suspended smectic-C* ( SmC(*)) films at the bulk SmC(*)-cholesteric ( N(*)) phase transition has been investigated using polarized-reflected-light microscopy. Our experimental observations show that above the bulk SmC(*)- N(*) phase transition the N(*) order appears in different ways according to the film thickness. In thin films, the conventional layer-by-layer thinning occurs. In films of intermediate thickness N(*) inclusions nucleate inside the SmC(*) film. The distortions of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 1 publication
3
44
1
Order By: Relevance
“…Dispersions are normally prepared by using well-controlled cycles of heating/cooling of free standing smectic films [90]. In order to initiate the nucleation of the lower order inclusions, the smectic film is gradually heated across the corresponding bulk transition temperature until the temperature of nucleation is reached.…”
Section: Inclusions In Free Standing Smectic Filmsmentioning
confidence: 99%
“…Dispersions are normally prepared by using well-controlled cycles of heating/cooling of free standing smectic films [90]. In order to initiate the nucleation of the lower order inclusions, the smectic film is gradually heated across the corresponding bulk transition temperature until the temperature of nucleation is reached.…”
Section: Inclusions In Free Standing Smectic Filmsmentioning
confidence: 99%
“…Optical analysis of the texture has revealed a radial c-director anchoring at the surface separating S C * and N* phases and the presence of a (−1)-wedge disclination in the neighbourhood of the inclusion [1][2][3]. The N* droplet can be represented by a (+1)-wedge disclination of finite length equal to the droplet length in the direction perpendicular to smectic layers.…”
Section: Introductionmentioning
confidence: 99%
“…The (−1)-wedge disclination corresponds to the notion of hyperbolic defect discussed in the Refs. [1][2][3]. Segments of (±1)-disclinations cannot terminate in the bulk of the film, but they are connected to form a disclination loop.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure and mechanical and thermodynamical properties of films have been widely studied since they were discovered by Friedel in 1922 [1,2]. Investigations of topological defects and the selforganization of circular inclusions in smectic C (SmC) free-standing films are quite recent [3][4][5][6][7][8]. Pettey et al [3] derived an expression for the director field associated with islands containing topological defects by minimizing the Frank elastic free energy of a smectic C film in 2D, assuming fixed boundary conditions on a circular disk on the film representing the island, and showed that there is a hyperbolic −1 point defect at a distance R 2 from the center where R is the disk radius.…”
Section: Introductionmentioning
confidence: 99%